The FACT Histone Chaperone: Tuning Gene Transcription in the Chromatin Context to Modulate Plant Growth and Development - Grasser, Klaus D. (Frontiers in Plant Science, 2020)
FACT is a heterodimeric histone chaperone consisting of the SSRP1 and SPT16 proteins and is conserved among eukaryotes. It interacts with the histones H2A-H2B and H3-H4 as well as with DNA. Based on in vitro and in vivo studies mainly in yeast and mammalian cells, FACT can mediate nucleosome disassembly and reassembly and thus facilitates in the chromatin context DNA-dependent processes including transcription, replication and repair. In plants, primarily the role of FACT related to RNA polymerase II transcription has been examined. FACT was found to associate with elongating Arabidopsis RNA polymerase II (RNAPII) as part of the transcript elongation complex and it was identified as repressor of aberrant intragenic transcriptional initiation. Arabidopsis mutants depleted in FACT subunits exhibit various defects in vegetative and reproductive development. Strikingly, FACT modulates important developmental transitions by promoting expression of key repressors of these processes. Thus, FACT facilitates expression of DOG1 and FLC adjusting the switch from seed dormancy to germination and from vegetative to reproductive development, respectively. In the central cell of the female gametophyte, FACT can facilitate DNA demethylation especially within heterochromatin, and thereby contributes to gene imprinting during Arabidopsis reproduction. This review discusses results particularly from the plant perspective about the contribution of FACT to processes that involve reorganisation of nucleosomes with a main focus on RNAPII transcription and its implications for diverse areas of plant biology.